2017
DOI: 10.1007/s13311-017-0551-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Approaches to Understanding Psychiatric Disease

Abstract: Human genetic studies have been the driving force in bringing to light the underlying biology of psychiatric conditions. As these studies fill in the gaps in our knowledge of the mechanisms at play, we will be better equipped to design therapies in rational and targeted ways, or repurpose existing therapies in previously unanticipated ways. This review is intended for those unfamiliar with psychiatric genetics as a field and provides a primer on different modes of genetic variation, the technologies currently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 249 publications
0
3
0
Order By: Relevance
“…Schizophrenia is known to have high heritability (60–90%; [ 85 , 86 ]) so ascertainment of specific risk genes is critical to understanding its etiology and pathophysiology. Three general approaches have been predominantly employed to detect specific genetic risk factors in schizophrenia studies: GWAS for common variants (each conferring very low risk); whole exome examination of ultra-rare coding variants (potentially conferring substantial risk); and rare CNVs (also with low risk; see O’Donovan et al [ 87 ] and Michaelson [ 88 ], for reviews on technical issues in psychiatric genetics [ 87 , 88 ]).…”
Section: Genetic Studiesmentioning
confidence: 99%
“…Schizophrenia is known to have high heritability (60–90%; [ 85 , 86 ]) so ascertainment of specific risk genes is critical to understanding its etiology and pathophysiology. Three general approaches have been predominantly employed to detect specific genetic risk factors in schizophrenia studies: GWAS for common variants (each conferring very low risk); whole exome examination of ultra-rare coding variants (potentially conferring substantial risk); and rare CNVs (also with low risk; see O’Donovan et al [ 87 ] and Michaelson [ 88 ], for reviews on technical issues in psychiatric genetics [ 87 , 88 ]).…”
Section: Genetic Studiesmentioning
confidence: 99%
“…During the past decade, rapid advances in high throughput technologies have helped investigators, aiming to uncover disease causal genes and their actions in complex diseases. Specifically, in psychiatric genetics, there have been numerous datasets from different platforms or sources such as association studies, including genome‐wide association studies, genome‐wide linkage scans, microarray gene expression, and copy number variation (Michaelson, ). Large‐scale and individual genetic studies revealed various polymorphisms and overexpression of certain genes in patients presenting with depressive symptoms (Lacerda‐Pinheiro et al, ; Milanesi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the complexity of this topic, the first article in this section, by Jacob Michaelson [4], provides an accessible overview of the field along with in-depth discussion of the applicat i o n o f g e n o m i c s t o s t u d y i n g t h e e t i o l o g y o f neurodevelopmental disorders. The second article in this section, by Benjamin Pickard [5], describes modern genomic approaches that are being used to identify and explore key differences between patients that do or do not respond to lithium.…”
mentioning
confidence: 99%